2023
DOI: 10.2147/prbm.s388394
|View full text |Cite
|
Sign up to set email alerts
|

Care Need Combinations for Dementia Patients with Multiple Chronic Diseases

Abstract: Purpose The purpose of this study was to find care need combinations for dementia patients with multiple chronic diseases and their caregivers. Patients and Methods A cross-sectional study was conducted with 83 patients who had multiple chronic diseases. Variables from patients included age, gender, severity of clinical dementia rating, feeding, hypnotics, mobility, getting lost, mood symptoms, and behavioral and psychological symptoms. Moreover, 26 types of care needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…There were 20,1936,35,661, and 2254 rules found for caregivers with severe burden, moderate-to-severe burden, mildto-moderate burden, and little or no burden, respectively. Studies had found that caregivers who cared for patients with dementia reported higher levels of depression and anxiety, engagement in fewer protective health behaviors, and were at an increased risk of medical illness and mortality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were 20,1936,35,661, and 2254 rules found for caregivers with severe burden, moderate-to-severe burden, mildto-moderate burden, and little or no burden, respectively. Studies had found that caregivers who cared for patients with dementia reported higher levels of depression and anxiety, engagement in fewer protective health behaviors, and were at an increased risk of medical illness and mortality.…”
Section: Resultsmentioning
confidence: 99%
“…19,32 When PLWD had MCCs, "care for the mood of the caregiver" should be considered especially in dementia patients with preserved ambulatory function or with symptoms of hallucination. 20 For patients with dementia, there were few reports showing that caregivers with a low education level had a higher caregiving burden. 22,30 For patients with frailty and MCCs, a nonsignificant trend of a higher burden was found in caregivers with higher education than those with informal education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations